Feasibility of 7T MRI for imaging fascicular structures of peripheral nerves. Issue 3 (22nd December 2017) - Yoon, Daehyun; Biswal, Sandip; Rutt, Brian; Lutz, Amelie; Hargreaves, Brian
ABSTRACT: Introduction : Evaluation of the nerve fascicular structure can be useful in diagnosing nerve damage, but it is a very challenging task with 3T MRI because of limited resolution. In this pilot study, we present the feasibility of high‐resolution 7T MRI for examining the nerve fascicular structure. Methods : A 3‐dimensional (3D) gradient‐spoiled sequence was used for imaging peripheral nerves in extremities. Images acquired with different in‐plane resolutions (0.42 × 0.42 mm vs. 0.12 × 0.12 mm), and different main field strengths (7T vs. 3T) were compared. Results : The individual nerve fascicles were identified at 0.12 × 0.12 mm resolution in both field strengths but not at 0.42 × 0.42 mm resolution. The fascicular structure was more sharply depicted in 7T images than in 3T images. Discussion : High‐resolution 3D imaging with 7T MRI demonstrated feasibility for imaging nerve fascicular structures. Muscle Nerve 57 : 494–498, 2018